Deggendorf: a lengthy slim gown a combination of porcelin-fine desig ns, pillow lace, two bands of pink prints on a white background
Shelf no.
Deggendorf: a lengthy slim gown a combination of porcelin-fine desig ns, pillow lace, two bands of pink prints on a white background, a boun cy flounce attached to the hem, togather with a low-sitting white corsa ge, trimmed with lace, and a mosaically patterned lap. all made of cott on only- is being dubbed as the provence style. It comes from Deggendor f a small city in the Bavarian Woods (Federal Republic of Germany), and is one of the most beautiful articles of outer attire that a young wom an could possibly wish to don.
AR/MAK PHOTOS/36/56
English
Keywords: Photography -- Germany; Photos -- Germany